Renewable energy strategy impacts on electricity system and carbon emissions in Hunan Province of China - Yang, Caixia; Xiao, Yao; Chen, Tao; Lei , Mingze; Wattana, Buncha (Edelweiss Applied Science and Technology, 2025)
This study investigates the impact of increasing renewable energy capacity on the power industry in Hunan Province, China, focusing on power demand, electricity generation, and CO2 emissions reductions. Using the Low Emission Analysis Platform (LEAP) model, five scenarios (BAU, RES, HEF, HST, and COP) were developed to assess the effects of renewable energy strategies from 2022 to 2035. The analysis considered renewable energy growth, energy storage, and efficiency improvements. The Comprehensive Optimization Scenario (COP) emerged as the most optimal, achieving a 48% share of renewable energy, 17% energy storage, and 23% efficient coal use, leading to significant CO2 emissions reductions while ensuring system flexibility and reliability. The study concludes that the COP scenario is the most effective in supporting a low-carbon transition and maintaining energy security. Practical implications include the need for policy support in areas such as diversified energy storage, distributed energy systems, V2G/V2X technologies, and smart grid development to enhance renewable energy integration and ensure sustainable development in Hunan.